Civil Service Reform in the States: Personnel Policy and Politics at the Subnational Level - J. Edward Kellough, Lloyd G. Nigro (State University of New York Press, 2006)
This book will examine the kinds of public personnel reforms noted above and the extent to which they are being implemented in state government. An assessment of reform at the state level is par- ticularly important given the significance of states in the delivery of public programs and the historic role the states have played as incu- bators of administrative change. The purpose here is to provide read- ers with a contemporary analysis and assessment of civil service reforms undertaken by state governments during the last decade of the twentieth century and the first years of the twenty-first. Some states have implemented dramatic reforms during that time, while in others, reforms have been resisted, often successfully. The chap- ters presented here were prepared for this volume by nationally rec- ognized experts on civil service and civil service reform in the United States, and we believe they will be of wide interest to public policy makers, practitioners, students, and academicians. In general terms, we sought a regional distribution of states and variation in history and politics that should be associated with attitudes toward reform. With these goals in mind, we selected states that had engaged in reform and others where reform efforts had been less successful. Our selections were also controlled by the availability of highly qualified authors who could speak knowledgeably about to the intricacies of civil service reform in each state. We expect this book will be useful as a text for advanced under- graduate and graduate courses on public administration and public personnel administration or human resources management. It is divided into two major sections. Part One, which is comprised of the first five chapters, examines the context of personnel reform in the states.